Is the Norwegian Army´'s View of Physical Education and Training Relevant for Modern Military Operations? - Boe, Ole; Nergård, John H. (International Journal of Learning, Teaching and Educational Research, 2017)
The demands of war consist of several dimensions that has to be considered during a military officer´s education and training. Considering the nature of modern military operations, physical training is an important dimension. Participating in modern military operations and wars is definitely a physically demanding task. The present study was conducted in order to answer the question whether the Norwegian Army´s view of physical education and training is relevant for modern military operations. In order to answer the research question in the present study, we used a qualitative method that included document analysis. The results of the document analyses yielded three interesting findings. First, we found that the Norwegian Army seems to learn to slow from its experiences from participating in military operations. Our second finding was that the physical demands in modern military operations seem to have increased. Our third finding was that individuals entering into military service in Norway seemed to be less robust than before. We therefore draw a conclusion that the Norwegian Army seem to be facing some challenges with physical education and training in relation to modern military operations.